Undergraduate Education Policy 2023: A Paradigm Shift Leading towards Practical Training - Hamid, Muhammad; Rehman, Atiq Ur (The Lighthouse Journal of Social Sciences, 2023)
Undergraduate Education Policy 2023 is the latest policy issued by the Government of Pakistan to cope with the epistemological, sociological and economic needs of society. It is issued in the continuity of the UGE Policy 2020. The UGE Policy 2023 Version 1.1 comprises guidelines for Bachelor of Studies (BS). Discussing mainstream general education (BS 4 years degree), the policy includes two segments of practical learning named as Field Experience and Capstone Project supported by the course Entrepreneurship. Both the practical segments are mandatory for the completion of degree and have weightage of 06 credit hours. It is a timely step to meet the demand of the preparation of productive human resource. By this, the policy, for the first time, has focused on the practical training of students at the undergraduate level, enabling them to know about their future role and worth. The article under study is based on the qualitative research and document analysis approach. It presents an analysis of the curriculum of BS in the light of the UGE Policy 2023. The policy has been compared to the earlier policies and plans issued for the Undergraduate level, too. Findings of the research show that the policy has aptly focused on the practical aspects of education which will lead towards economic productivity and professional skillfulness of the students. The outcome of the policy will certainly be very encouraging if implemented in true spirit.